THEORETICAL FUNDAMENTALS OF WORKING ON THE TEXT IN READING LESSONS (Archive of Conferences, 2021)
The Primary Reading Book contains popular art and science articles in a variety of genres. We know that in a work of art, life is represented through images. At its center is man, his relationship to nature and society. The rules of depiction of existence, reality in the work of art through images, objective content and subjective assessment in concrete material are of great theoretical and practical importance for the methodology